MEMBACA GAMBAR BERPIKIR VISUAL - Drs. Baskoro Suryo Banindro (Ars: Jurnal Seni Rupa dan Desain, 2007)
Reading a picture is no different to reading verbal text. The brain sensors o f the obsener willidentify and the psyche will translate the results differently based on the references and experiences o f theaudience. Technical illustration as an element o f visual language has its own illusive property because thecomponents are assembled from a mechanical series. This technical illustration should enable to provide athree-dimensional visual information on the material composite, the works, and placement.Keywords: Technical illustrations, visual information, monosemic, three-dimensional.